(untitled) (East West Medical College Journal, 2026)
Background: Fracture shaft of femur is a common fracture in children, with treatment from conservative in form of skin traction to intramedullary nailing depending on age. Conservative treatment is mostly used upto six years of age, while for children more than 12 years surgery is usually preferred. Objective of the study was to evaluate the result of skin traction of isolated femoral shaft fracture in children. Methods: Study was done in international medical college hospital,Gazipur from july 2021 to May 2025. 17 patients were enrolled for study, patients were initially given skin traction to get alignment . Patients age 2 to 5 years, with a mean age of 3.7 years range with closed isolated femoral shaft fractures were included in the Study. Patients having compound fractures and those with polytrauma were excluded from the study. Follow up was done in OPD after 1,4,8,12,24 weeks with check x-rays taken at every visit. Results: 17 patients were included for study , male 11 (64.7%), female 6 (35.3%) . Average age of children was 3.7 years. Mode of trauma was mostly RTA 11 (64.7%), fall from height 3 (17.6%), fall from bicycle 3 (17.6%). Average duration of traction was 17.5 ( 14-26) days and average stay in hospital was 15.5 days. Average union time was 8.2 weeks. Conclusion : Skin traction is a easy, safe, and non-invasive treatment way for femoral shaft fractures in children in 2 to 5 years , no anesthesia is needed. EWMCJ Vol. 14, No. 1, January 2026: 67-70